2019
DOI: 10.1093/ons/opz082
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Fluorescence-Guided Resection Increases Radicality in Glioblastoma Surgery

Abstract: BACKGROUND Several studies have proven the benefit of a greater extent of resection on progression-free survival and overall survival in glioblastoma (GBM). Possible reasons for incomplete tumor resection might be wrong interpretation of fading fluorescence or overseen fluorescent tumor tissue by a lacking line of sight between tumor tissue and the microscope. OBJECTIVE To evaluate if an endoscope being capable of inducing fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…After publication of a technical note in 2014, a first clinical series showed that residual fluorescent tumor tissue not visualized with the microscope could be detected with endoscopic assistance. 6,10 This finding is not surprising because inducing fluorescence is mainly related to adequate exposure to blue light. According to the inversesquare law ("illumination of a surface receiving its flux from a point source is inversely proportional to the square of the distance between the surface and the source"), the endoscope, as compared to the microscope, is capable of significantly reducing the distance between the light source and the tissue.…”
Section: Impact On Eormentioning
confidence: 89%
See 4 more Smart Citations
“…After publication of a technical note in 2014, a first clinical series showed that residual fluorescent tumor tissue not visualized with the microscope could be detected with endoscopic assistance. 6,10 This finding is not surprising because inducing fluorescence is mainly related to adequate exposure to blue light. According to the inversesquare law ("illumination of a surface receiving its flux from a point source is inversely proportional to the square of the distance between the surface and the source"), the endoscope, as compared to the microscope, is capable of significantly reducing the distance between the light source and the tissue.…”
Section: Impact On Eormentioning
confidence: 89%
“…According to the inversesquare law ("illumination of a surface receiving its flux from a point source is inversely proportional to the square of the distance between the surface and the source"), the endoscope, as compared to the microscope, is capable of significantly reducing the distance between the light source and the tissue. 6 Besides the barriers of the depth of the surgical field, the presence of overhanging tissue or collapse of the resection cavity can lead to insufficient visualization of the tumor margins. 12 Furthermore, blind spots for microscopic FG resection can exist in the area of the craniotomy 10 as well as at the margin of the tumor due to collapse of the resection cavity.…”
Section: Impact On Eormentioning
confidence: 99%
See 3 more Smart Citations